Regional strategy and its features in the conditions of market economy - Myroshnyk, N. V. (Science and Transport Progress, 2012)
The term “region” is defined. It is studied that in the conditions of modern market economy for an effective management of financial resources it is necessary providing the enterprise activities with optimal amount of these resources, their rational use, maximization of income and providing the appreciation of market enterprise value. In such conditions the issues of improvement of management of production processes, the effective use of financial, labor, and material resources become topical. The transition to the modern market economy caused the changes of all the economic system and, for the first, regional enterprises. The terms of managing the economy suffered transformations, which found an expression in the changes of ownership patterns, the terms of government control, and the tax system. The non-public sector of economy appeared as a result of reforms, modern banking system, markets of commodities, services, capital. It gives an opportunity for the reproduction on an expanded scale, the increase of enterprise profits, and the income of its proprietors. One is able to achieve this goal only under the optimal management of finances. In the modern conditions of managing the economy the control system is to be migrated to regions differing one to another in national, historical, geographical, economic and other peculiarities. A structural policy that must foresee the transition of state economy to a new resource-provided, hi-tech and economically safe model of operation is realized in Ukraine. Establishing in the country of free economic zones, where the favourable custom, currency-financial, tax and other conditions of economic activity are in force, is very promising. The territorial social-and-economic structure of Ukraine is based upon the principles of unity and integral state power, an appropriate balance of socio-economic development of separate territories taking into account historical and cultural traditions, demographic and ecological features. In a regional challenge, there is a task: what is the aid addressee – the depressive region or its population? If the former then investments are necessary, the latter – promoting the population migration to more solvent regions is better. But even the most backward region is a motherland of part of population and that is why it deserves to get this aid.